Differential Mechanism of Periodontitis Progression in Postmenopause - Lee, Dong-Joon; Wu, Lei; Shimono, Masaki; Piao, Zhengguo; Green, David W.; Lee, Jong-Min; Jung, Han-Sung (Frontiers in Physiology, 2018)
Over the past four decades, it has become accepted that periodontal disease is caused by specific bacterial infections and that individuals are uniformly susceptible neither to these infections nor to the damage caused by them. The specific bacterial infections and the composition of the environment in which these bacteria easily settle cause an immune response. The immune cells involved in pathogenesis of periodontitis migrate into the periodontitis lesion and advance the disease. The purpose of the present study is to investigate the correlation between immune cell migration and progression of periodontal disease by inducing estrogen deficiency through ovariectomy (OVX) to mimic postmenopausal women and treatment with lipopolysaccharide (LPS). The LPS derived from Porphyromonas gingivalis induced periodontitis and absorption of the alveolar bone dose-dependently. However, the alveolar crest level reduction after LPS injection between OVX and Sham operated mice did not show a significant difference. Matrix metallopeptidase-9 (MMP-9), which is known to be able to detect the progression of periodontitis in general, was not significantly different between OVX and Sham groups. However, immune cells such as T-lymphocytes and neutrophils migrated less overall in OVX groups than Sham operated groups. These findings can be a topic of debate on the old controversy regarding the relationship between periodontal disease and hormonal change. Currently, in clinical practice, menopause is not a major consideration in the treatment of periodontal disease. This study suggests that treatment methods and medication should be considered in the treatment of infectious periodontal disease in postmenopausal women.